Binding of the Cyclophilin 40 Ortholog SQUINT to Hsp90 Protein Is Required for SQUINT Function in Arabidopsis - Earley, Keith W. (American Society for Biochemistry and Molecular Biology, 2011)
SQN (SQUINT) is the Arabidopsis ortholog of the immunophilin CyP40 (cyclophilin 40) and promotes microRNA activity by promoting the activity of AGO1. In animals and Saccharomyces cerevisiae, CyP40 promotes protein activity in association with the protein chaperone Hsp90. To determine whether CyP40 also acts in association with Hsp90 in plants, we examined the interaction between SQN and Hsp90 in vitro and tested the importance of this interaction for the function of SQN in planta. We found that SQN interacts with cytoplasmic Hsp90 proteins but not with Hsp90 proteins localized to chloroplasts, mitochondria, or the endoplasmic reticulum. The interaction between SQN and Hsp90 in vitro requires the MEEVD domain of Hsp90, as well as several conserved amino acids within the tetratricopeptide repeat domain of SQN. Amino acid substitutions that disrupt the interaction between SQN and Hsp90 in vitro also impair the activity of SQN in planta. Our results indicate that the interaction between CyP40 and Hsp90 is conserved in plants and that this interaction is essential for the function of CyP40.